Сriterion of falsifiability in the research work - N. I. Martishina (Высшее образование в России, 2022)
The content of falsifiability principle as a criterion of science formulated by Karl Popper is considered. The practical value of this criterion in the research work is described. Practicalrecommendations are formulated.